A survey on collections of audiovisual materials in selected media centers in Quezon City - Quinto, Mae Lyn P.; Gonzales, Grace Marie B. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2008)
The study attempted to study the audiovisual materials administration of Media Centers in selected private high schools in Quezon City. Specifically, it aimed to identify the audiovisual materials and equipment available in the Media Centers, the selection and acquisition, cataloging and classification and utilization of audiovisual materials, audiovisual materials used by the teachers as instructional tools, assessment by teachers of the existing audiovisual collection and its services; and lastly, determine the collaboration of media specialists and teachers in terms of growth and utilization of the audiovisual materials.
The population was composed of six private high schools found in Quezon City, these were: 1) Immaculate Conception Cathedral School, (2) Our Lady of the Sacred Heart School, 3) School of Saint Anthony, 4) Diliman Preparatory School, 5) Philadelphia High School, and 6) Jose Abad Memorial School (JASMS). Questionnaires were distributed to the head of the media center and one teacher of each subject of Math, Science, English, Social Studies and Pilipino. Two different questionnaires were prepared for the media specialist and teachers. A follow-up telephone interview to the media specialists was also conducted. Videotapes are the most common audiovisual software in the media center. Majority of the media specialist identified teachers as the initial school personnel involved in selecting audiovisual materials. The media specialists coordinate with the purchasing officer of the school in purchasing the audiovisual material and equipment. The acquired audiovisual materials are being arranged by the media specialist by providing accession and class numbers when these materials are being cataloged and classified. Science teachers prefer to use videotapes and other audiovisual software like videodisc, videotapes, electronic resources, cassette tapes, sound disc and slides. Cassette tapes are the most common audiovisual software materials for English and Filipino teachers. Usually, cassette tapes are being used in speech classes as stated in the survey. Five out of six media specialists said that the teachers openly discuss to them the instructional materials they need in their class like books, audiovisual materials and journals.
Based on the findings, the following recommendations are drawn: 1) The Media specialists should assert leadership in using technology and other educational tools such as audiovisual materials to the school administrators and teacher. In this manner, students of their schools will learn to be responsible consumers and producers of information at an early age. 2) School library media centers have to re-evaluate their present program. The program should be dynamic and student-centered that foster information literacy and lifelong learning. 3) Media specialists should always be an active instructional partner of teachers in order to fulfill the demands of students in this information age. In turn, the growth of the collection will be addressed always. 4) Extensive studies in the future should be conducted win an endorsement of the Department of Education in order to have a smooth to at least 25 of private schools in Quezon City as part of the population. In this manner, ideal and concrete data on audiovisual materials in the media centers will be attained. All subjects offered in the high school level including PE, health, home economics and values education should also be part of the study to provide a concrete picture of audiovisual materials use in the teaching learning process.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Audio-visual materials -- Philippines -- Quezon City; Instructional materials centers -- Collection development -- Philippines -- Quezon City; Audio-visual library service -- Philippines -- Quezon City; High schools -- Philippines -- Quezon City